INTEGRASI ASPEK LINGKUNGAN DALAM PENENTUAN KELAYAKAN USAHA BERKELANJUTAN - Hersiyah; Rohman, Abdur (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
Business sustainability has increasingly become a central concern in economic decision-making. This study aims to analyze how environmental aspects can be integrated into business feasibility studies to ensure long-term sustainability. The methodology employs a multidisciplinary approach that considers economic, social, and ecological factors. The findings indicate that integrating environmental considerations into feasibility analyses not only enhances resource efficiency but also reduces negative impacts on ecosystems. Key factors such as waste management, the use of renewable energy, and compliance with environmental regulations play a crucial role in supporting sustainable enterprises. Therefore, this study provides recommendations for business actors and stakeholders to adopt environmentally based strategies in business planning.